Why ammonium detection is particularly challenging but insightful with ionophore-based potentiometric sensors – an overview of the progress in the last 20 years. Issue 9 (2nd April 2020) - Cuartero, María; Colozza, Noemi; Fernández-Pérez, Bibiana M.; Crespo, Gastón A.
Abstract : An overview of ionophore-based electrodes for ammonium sensing critically analyzing contributions in the last 20 years and with focus in analytical applications. Abstract : The monitoring of ammonium ion concentration has gained the attention of researchers from multiple fields since it is a crucial parameter with respect to environmental and biomedical applications. For example, ammonium is considered to be a quality indicator of natural waters as well as a potential biomarker of an enzymatic byproduct in key physiological reactions. Among the classical analytical methods used for the detection of ammonium ions, potentiometric ion-selective electrodes (ISEs) have attracted special attention in the scientific community because of their advantages such as cost-effectiveness, user-friendly features, and miniaturization ability, which facilitate easy portable measurements. Regarding the analytical performance, the key component of ISEs is the selective receptor, labelled as an ionophore in ISE jargon. Indeed, the preference of an ionophore for ammonium amongst other ions ( i.e., selectivity) is a factor that primarily dictates the limit of detection of the electrode when performing measurements in real samples. A careful assessment of the literature for the last 20 years reveals that nonactin is by far the most employed ammonium ionophore to date. Despite the remarkable cross-interference of potassium over the ammonium response of nonactin-based ISEs, analytical applications comprising water quality assessment, clinical tests in biological fluids, and sweat monitoring during sports practice have been successfully researched. Nevertheless, there is evident difficulty in the determination of close-to-micromolar levels of ammonium in real samples with a significant potassium background level ( i.e., millimolar concentration). This fact has fostered the search for a large variety of ammonium ionophores over the years, which are critically inspected herein. Overall, we provide an easily readable state of the art accompanied by a comprehensive description of other types of ammonium electrodes, including commercially available units. We conclude that newer breakthroughs are still required in the field to reach the desired analytical applications.